The power of potential natural vegetation (and of spatial‐temporal scale): a response to Carrión & Fernández (2009) - Emmanuele Farris; Goffredo Filibeck; Michela Marignani; Leonardo Rosati (Journal of Biogeography, 2010)
A commentary by Carrión & Fernández ( Journal of Biogeography , 2009, 36 , 2202–2203) compared Holocene pollen records with models of potential natural vegetation (PNV) proposed in the phytosociological literature and concluded that the predicted PNV resulted from anthropogenic disturbance. However, the authors misinterpreted PNV, leading to two serious flaws in their assumptions: (1) PNV is not defined as a pre‐anthropic or climax plant community; and (2) PNV is not a concept restricted to the phytosociological method. Therefore we criticize the conclusions expressed in the commentary, and we stress the need for an interdisciplinary approach based on multi‐temporal and multi‐spatial scales to achieve a modern framework for the study of plant communities.